Determining Sport Concussion Assessment Tool fifth Edition (SCAT5) reliable change in male professional hockey players - Bruce, J. M.; Meeuwisse, W.; Hutchison, M. G.; Comper, P.; Echemendia, R. J. (British Journal of Sports Medicine, 2022)
Objectives: The purpose of this paper is to provide reliable change metrics and assess the test-retest psychometrics of the Sport Concussion Assessment Tool fifth Edition (SCAT5) in a multilingual sample of professional ice hockey players.Methods The SCAT5 was administered to National Hockey League and American Hockey League male professional ice hockey players as part of the 2018 and 2019 season medical evaluations. We extracted data from an existing clinical database of players who were administered two consecutive baseline evaluations and had no intervening concussions to assess psychometric properties (eg, test-retest reliability) and develop reliable change metrics.